THU0014 Twenty-Year Follow-Up of Brain MRI in A Series of Patients with Systemic Lupus Erythematosus. (10th June 2014) - Piga, M.; Peltz, T.M.; Perra, D.; Montaldo, C.; Vacca, A.; Garau, P.; Ibba, V.; Porru, G.; Figus, F.; Gabba, A.; Cauli, A.; Mathieu, A.
Abstract : Background: Conventional MRI (cMRI) is a first level investigation in the diagnostic work-up of Systemic Lupus Erythematosus (SLE) patients with neuropsychiatric (NP) manifestations. Objectives: To evaluate the long-term evolution of cerebral abnormalities by (cMRI) in patients with SLE. Methods: Thirty patients (29F, age 53.5±11.3 yrs, disease duration 24.9±6.7 yrs) with SLE were prospectively observed and brain MRI studies (T1, T2, GRET*2 and FLAIR sequences) were obtained at baseline (MR-1 - 0.5 Tesla) and repeated after 19.4±3.7 yrs of follow-up (1.5 Tesla – MR-2). An experienced neuroradiologist analyzed the MRI comparing the following outcomes: 1) number of focal subcortical white matter hyperintensity (WMHI) lesions, 2) presence of parenchymal defects secondary to large-vessel ischemic lesions, 3) cerebral atrophy visually assessed and quantified using the Evans' index. Cumulative MRI brain damage was calculated according to a modified scoring system proposed by Petri et al (1). Each patient was assessed for the presence of NP manifestations SLE-related (NP-SLE) or unrelated (NP-nonSLE), according to criteria proposed by the Italian Study Group on NP-SLE (2). Demographic, clinical and serological data were also recorded in order to identify risk factors associated with worsening of brain MRI abnormalities. Multiple stepwise regression analysis were applied. P-values <0.05 were considered significant Results: Twenty patients (66.6%) had an increased number of focal WMHI lesions whilst 8 patients (26.7%) showed a significant increase of Evans' index, defined as an increase greater than the sample mean + standard deviation. Modified Petri's score worsened in 23 patients (76.7%) and when the entire cohort was considered the difference between baseline and follow-up resulted statistically significant (MR-1: 1.3±1.5 vs. MR-2: 2.9±2.1; p<0.0001). Brain MRI showed parenchymal defects secondary to large-vessel ischemic lesions in 6 patients (20%) 4 of which were not present at baseline. Previous WMHI lesions on MRI (p=0.016; OR 231.4 and 95%CI: 2-1980) resulted as the only independent risk factor for the development of new WMHI lesions, whilst treatment with antimalarials (p=0.004; OR 0.01 and 95%CI: 0.0-0.25) was independently associated with a reduced risk. Hyperlipidemia (p=0.044; OR 10.1 and 95%CI 1.1-97.0), resulted independently associated with an increased risk to develop cortical atrophy. Finally, a cumulative steroids dose higher than 50 grams (p=0.026; OR 8.8 and 95%CI 1.2 – 61.0) was the only independent risk factor for increase in cumulative brain MRI damage. Twenty-one patients reported at least one NP event (7pts had >1 event). Fourteen patients were classified as NP-SLE and 7 as NP-nonSLE. The only independent risk factor for new NP-SLE manifestation was a previous NPSLE event (p=0.015; OR 10.2 95%CI 1.5 – 67.2) whilst higher modified Petri's score was an independent risk factor for the development of NP manifestations of any nature. Conclusions: Worsening of MRI brain damage in SLE patients is related to risk factors both linked and not linked to the disease and it is associated with the risk of new NP events of any nature. References: Petri M et al. J Rheumatol. 2008;35:2348-2354. Govoni M et al. Rheumatology (Oxford). 2012;51:157-68. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4488